Efecto de bacterias diazótrofas y su importancia para el rendimiento de los cultivos de ciclo corto - García Castro, Joel Darwin (2022)
Soils for crop production often suffer from frequent degradation and consequently medium fertility; This has caused low yields per surface unit, which also affects the economic income of the producers. The indiscriminate use of chemical products in crops has caused environmental contamination and in the health of the population, being essential the use of products based on microorganisms, which have not been studied in depth and that farmers by belief doubt their effectiveness. The conclusions determine that the native microorganisms with properties that promote plant growth are Azotobacter, Burkholderia and Azospirillum, considered as biofertilizers in crops of agronomic interest; the isolation of diazotrophic bacteria, their identification by reliable methods and the evaluation of their ability to promote plant growth, in addition to being an option in research processes for agricultural purposes, is a good alternative to improve the nutrition and quality of crops, which contributes to the improvement of the plant-soil-microorganism system; the bacteria Azospirillum sp. and Azotobacter sp. have been reported as plant growth promoters in plants obtaining increases in growth parameters, root length, height and production and the effect of the bacterium Azotobacter sp. It is evident from the beginning of the crop, increasing the number of seedlings in seedbeds, height growth, number of leaves, stem diameter, leaf area and plant biomass, making it possible to shorten the harvest cycle in crops by 7-10 days. short cycle.